2018
DOI: 10.1155/2018/7394268
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma Origin and Therapeutic Targets for Immunotherapy

Abstract: Neuroblastoma is a pediatric solid cancer of heterogeneous clinical behavior. The unique features of this type of cancer frequently hamper the process of determining clinical presentation and predicting therapy effectiveness. The tumor can spontaneously regress without treatment or actively develop and give rise to metastases despite aggressive multimodal therapy. In recent years, immunotherapy has become one of the most promising approaches to the treatment of neuroblastoma. Still, only one drug for targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
106
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 251 publications
(267 reference statements)
0
106
0
9
Order By: Relevance
“…Gangliosides, including GM2 or GD2, belong to the family of glycosphingolipids (GSL) and contain one or more sialic acids, N-acetyl derivatives of neuraminic acid, in their hydrophilic oligosaccharide chain. 13 Gangliosides are sialic acid-containing glycosphingolipids that are most Results GM2/GD2 expression status in melanoma and neuroblastoma cell lines. To assess the GM2/ GD2 expression level, four melanoma (A-375, RPMI-7951, WM115 and SH4) and two neuroblastoma cell lines (IMR32 and RTBM1) were measured by flow cytometry.…”
mentioning
confidence: 99%
“…Gangliosides, including GM2 or GD2, belong to the family of glycosphingolipids (GSL) and contain one or more sialic acids, N-acetyl derivatives of neuraminic acid, in their hydrophilic oligosaccharide chain. 13 Gangliosides are sialic acid-containing glycosphingolipids that are most Results GM2/GD2 expression status in melanoma and neuroblastoma cell lines. To assess the GM2/ GD2 expression level, four melanoma (A-375, RPMI-7951, WM115 and SH4) and two neuroblastoma cell lines (IMR32 and RTBM1) were measured by flow cytometry.…”
mentioning
confidence: 99%
“…The high heterogeneity of NB derives from its transient embryonic structure, leading to a wide range of cellular phenotypes, sometimes present even in a single tumor (Aygun, 2018). The phenotypic analysis has uncovered miscellaneous types of highly expressed surface markers that can also act in tumorigenesis or contribute to progression of the oncologic process [e.g., CD117, CD133, CD114, CD57, CD171, or disialoganglioside 2 (GD2)] (Malone and Stegmaier, 2017;Kholodenko et al, 2018).…”
Section: Therapeutic Strategies In Neuroblastoma: Targeting High-riskmentioning
confidence: 99%
“…This immunotherapeutic approach is in many cases administered along with interleukin-2 and isotretinoin in the maintenance therapy. Clinicians have reported that the combination of this anti-GD2 antibody with other therapies increased the 5-year survival rates of NB patients by 20% (Kholodenko et al, 2018). An incoming Children's Oncology Group trial is planning to include immunotherapy in the induction stage to evaluate the benefits when combined with chemotherapy.…”
Section: Therapeutic Strategies In Neuroblastoma: Targeting High-riskmentioning
confidence: 99%
“…Neuroblastoma (NB) is the most common extracranial solid tumor in children, accounting for 7% of all pediatric tumors in patients under 15 years of age, and 15% of all pediatric deaths caused by cancer. The world mortality rate is 0.85-1.1 per 100,000 children under 15 years of age [1]. At present, the overall survival rate (OS) of low-and medium-risk NB is above 90% [2,3].…”
Section: Introductionmentioning
confidence: 99%